One Health community of practice monthly webinar series - CGIAR Research Program on Livestock (2020)
The Community of Practice (COP) is up and running within the One Health for Humans, Environment, Animals and Livelihoods (HEAL) project, supported by bilateral donors and the Livestock CRP.